Economic value of forest ecosystems in the Nipa-Nipa Grand Forest Park, Southeast Sulawesi, Indonesia - SAFRIL KASIM; TRI ASTUTI; ABHISHEK AGARWAL; HASDDIN HASDDIN; LA FARIKI; NURDIN SULISTIYONO; LA ODE RUSTAM; NUR ASIZAH; FAJAR SARANANI; AHMAD AHMAD (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kasim S, Astuti T, Agarwal A, Hasddin, Fariki L, Sulistiyono N, Rustam LO, Asizah N, Saranani F, Ahmad. 2024. Economic value of forest ecosystems in the Nipa-Nipa Grand Forest Park, Southeast Sulawesi, Indonesia. Biodiversitas 25: 4292-4303. The economic value of ecosystem services is crucial for development planning that prioritizes the sustainability of natural resources. Research aimed at determining the economic value of forest ecosystems is very important. The total economic value of this ecosystem is based on the number of tourist visits, utilization of water resources, and carbon absorption. The research was conducted in the Nipa-Nipa Grand Forest Park, Southeast Sulawesi Province, Indonesia. The research sample was 150 visitors selected using incidental techniques. The main data of the research used surveys and field measurements supported by secondary data. The TEV equation calculates the total economic value of forest ecosystem services. The monetary value of water resource environmental services is based on Household Water Value (NART), EWTP, and TWTP. The value of water resources for agricultural irrigation is calculated using the Water Value for Rice Agricultural Irrigation (NAUT) equation. The carbon absorption value is determined using the Carbon Uptake Value (CAV) equation. The total economic value of environmental services based on the number of visits, utilization of water resources, and carbon absorption capacity is IDR 186,742,287,967 per year or USD 11,694,269.91 per year. This value is equivalent to 40% of the GRDP of the forestry business sector in Southeast Sulawesi Province. Theoretically, this further emphasizes the importance of environmental services in the economy and human survival. Further research should focus on calculating the value of carbon absorption according to vegetation type and carbon stock to see the balance curve.